Identifying Suitable Environments for Autonomous Truck Development A Study on Controlled Outdoor Environments and Their Characteristics - Björck, Lorenzo; Gunnarsson, Moa (My University, 2023)
As the transportation industry is struggling with several structural problems, autonomous trucks have emerged as one potential solution to the issues such as driver shortage, shrinking margins and climate change. As of today, there is low technical maturity in autonomous solutions, and due to this the developers are struggling to find well-suited locations for the technology’s primary implementation. In light of this issue, several authors have turned attention to controlled outdoor environments as a potential arena for deployment of autonomous trucks, suggesting that these sites may be easier to operate than public environments. Despite this interest, there exists no comprehensive compilation of which types sites these potential controlled outdoor environments would consist of, when placing them in the context of autonomous trucks. Moreover, there is a lack of knowledge about which characteristics these controlled outdoor environments exhibit that make them suitable for autonomous trucks. In light of this, this report investigates both which characteristics of controlled outdoor environments that predisposes suitability, as well as identifying which of these controlled outdoor environments exhibit the characteristics that supports the operations of autonomous trucks. During the research, it was found that there were both site specific characteristics and general characteristics. The first category of characteristics were divided into the categories vehicle requirements, size of automation opportunity, traffic environment, operational conditions and site actor attitudes. Subsequently, the general characteristics were divided into weather conditions, regulatory conditions, economic conditions and autonomous loading and unloading. Moreover, the site types assessed by the study were dry ports, manufacturing plants, ports, intermodal terminals, transshipment centers, freight village/logistics clusters and airports. Both the impact of characteristics and the sites were discussed from several dimensions, namely use case, profitability, safety and regulatory conditions. Key characteristics from a deployment perspective was the internal transport volume on a site, its physical size, cargo type and form factor requirement, weather conditions as well as if the site was fenced-off. As for the evaluation of site types, ports stand out from the other sites due to their suitability on all dimensions, although they have specific requirements for vehicle capacity and performance. Next in line in terms of suitability are manufacturing plants, freight villages and airports. Finally, the report concluded that there is large internal variation between individual sites of the same type, and therefore it is important to study each site individually prior to a deployment decision.
Keywords: controlled outdoor environments; autonomous trucks; deployment factor; technology adoption; site characteristic